Gender and Spatial Variations in the Use of Digital Media Related to Adolescents Reproductive Health in Yogyakarta Post-Pandemic Covid-19 - Wiwik Puji Mulyani; Mitha Safira (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2023)
Teenagers have an essential role as part of the development. The proportion of youth ranks highest in the overall population in the world, including Indonesia. The development of the digital world occurs along with the transition of adolescent life which has both good and bad impacts. The impact of the Covid-19 Pandemic became an accelerator for increasing the utility of youth towards digital media. The increase in risky behavior due to technological developments carried out by adolescents raises concerns. On the other hand, technological developments can also positively impact increasing knowledge and attitudes/behaviors, especially regarding health and reproductive issues which are closely related to adolescent development. The purpose of this study was to analyze the knowledge and attitudes/ behaviors of adolescents related to reproductive health, adolescent characteristics and differences in adolescent knowledge according to their demographic characteristics and to analyze the use of digital media for Communication, Information, and Education (IEC) for post-pandemic adolescent reproductive health. This research is quantitative research and the unit of analysis used is the individual level (adolescents). The number of samples was 130 youth and data were analyzed by descriptive quantitative. The results of the study show that adolescents’ knowledge of reproductive health is in a good category, but still needs to be improved. Likewise, regarding attitudes and behavior, there are a few teenagers who have attitudes and behaviors which are vulnerable to problems, such as the consumption of alcohol, cigarettes, drugs, free sexual relations, and others. There are four major digital platforms which are often used and teenagers are comfortable using them to access reproductive health knowledge and information, specifically online mass media, Instagram (IG), Tiktok, and Youtube.